1959
DOI: 10.1103/physrev.115.1374
|View full text |Cite
|
Sign up to set email alerts
|

Linked-Diagram Expansions for Quantum Statistical Mechanics

Abstract: A general method of calculation is described for quantum statistical mechanics. It is based on a simplification of the Laplace transform of the density matrix which follows from a theorem due to Hugenholtz. The basic result is that an element of the density matrix can be written as a sum over graphs, with the contribution of each graph factored into contributions from connected or linked graphs. Applied to the grand partition function, the exponential formula of Bloch and deDominicis is obtained in a simple wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1960
1960
1986
1986

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Glassgold et al (5) have proposed a model for explaining the mechanism of nucleon production through the excitation of shock waves in the target nucleus, induced by a very high energy impinging hadron. This model predicts that the peak of the angular distribution of the nucleons emitted through the excitation of the shock waves must be at an angle, 80, considerably distant from the forward direction.…”
Section: ) L N E Pmentioning
confidence: 99%
See 3 more Smart Citations
“…Glassgold et al (5) have proposed a model for explaining the mechanism of nucleon production through the excitation of shock waves in the target nucleus, induced by a very high energy impinging hadron. This model predicts that the peak of the angular distribution of the nucleons emitted through the excitation of the shock waves must be at an angle, 80, considerably distant from the forward direction.…”
Section: ) L N E Pmentioning
confidence: 99%
“…Finally, it may be concluded that the cascade-evaporation mechanism of nucleon production is involved in disintegrations having Nh < 28 in high-energy hadron-nucleus interactions, whereas for the events with Nh 2 28, the nucleon production is envisaged to take place through the excitation of nuclear shock waves in the target nucleus by very energetic incident particles. The mean normalized multiplicity, RA, is defined as grey particles produced in high-energy hadron-nucleus interactions (5). This discrepancy in the observed distributions of grey particles in both the usual hadron-nucleus interactions Can.…”
Section: ) L N E Pmentioning
confidence: 99%
See 2 more Smart Citations
“…This situation is analogous to the interaction potential between a nucleon and an anti-nucleon. 4 ) Glassgold, Heckrotte and Watson 2 ) studied a similar problem, but they did not take HJ (2).…”
Section: )1mentioning
confidence: 99%